X-Ray Absorption Fine Structure of Ti Coordination Changes in Na2O-B2O3-SiO2-TiO2 Glass System - Zhao, Yingna; Zeng, Xiongfeng; Zhang, Wenli; Jin, Jianguo (Asian Journal of Chemistry, 2015)
The Na2O-B2O3-SiO2-TiO2 glass was prepared by adding 8 wt % TiO2 into the basic glass 10Na2O-50B2O3-40SiO2 (mol %). Application Ti K-edge X-ray absorption fine structure (XAFS), the change of Ti structure during the glass phase separation process was mainly investigated. Glass phase separation and TiO2 crystallization of the samples were characterized by X-ray diffraction, scanning electron microscope and transmission electron microscope. The results indicated that Ti4+ formed [TiO4] tetrahedral structure in high-temperature homogeneous glass of Na2O-B2O3-SiO2-TiO2 system. At low temperature heat treatment (500 °C) Ti4+ entirely transformed from [TiO4] to [TiO6] and then formed nucleus pre-group and anatase crystal nucleus, which were advantageous to crystallize TiO2. With the increasing of heat-treatment temperature, Ti-ion structure is closed to that of anatase and TiO2 began to crystallize at heat-treatment 550 °C.